Cervical nystagmus due to loss of cerebellar inhibition on the cervico-ocular reflex: a case report. Issue 2 (February 1985) - Bronstein, A M; Hood, J D
Abstract : Studies of the cervico-ocular reflex and the vestibulo-ocular reflex have been carried out separately and in combination on a patient with gait ataxia due to a cerebellar tumour. With the head fixed in space, body rotation to the right (left neck torsion) induced marked nystagmus to the left in darkness. Vestibulo-ocular responses to sinusoidal rotation were symmetrical while the neck was immobilised and asymmetric when it moved freely. It is suggested that the cervical nystagmus seen in this case was the result of removal of cerebellar inhibition upon the cervico-ocular reflex and that abnormal interaction of cervical and vestibular inputs could have played a role in the patient's unsteadiness.